1964
DOI: 10.1017/s0025315400024954
|View full text |Cite
|
Sign up to set email alerts
|

A Revised Check-List of British Marine Algae

Abstract: The Preliminary Check-list (Parke, 1953), with the three subsequent lists of additions and corrections (Parke, 1956, 1957, 1959) was intended to provide a fundamental basis for the preparation of a Flora of the British marine algae sponsored by the British Phycological Society. Changes, both taxonomic and systematic, have been so numerous in recent years that a new Check-list is now necessary for the six Classes dealt with in 1953. Five additional Classes, marked below with an asterisk, are also included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
2

Year Published

1967
1967
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 62 publications
2
106
0
2
Order By: Relevance
“…The last two species, R. litoralis and R. maritima, were transferred to Ruttnera on the basis of their flagellar structure (Parke & Dixon, 1964). Material corresponding closely to Gloeochrysis litoralis Anand and G. maritima Anand (Anand, 1937) was observed to produce swarmers of the ochromonad type, comparable with Ochromonas oblonga Carter (Carter, 1937), in contrast to the Chromulina-likc motile cells described for the type species of Gloeochrysis, G. pyrenigera Pasch.…”
Section: Discussionmentioning
confidence: 99%
“…The last two species, R. litoralis and R. maritima, were transferred to Ruttnera on the basis of their flagellar structure (Parke & Dixon, 1964). Material corresponding closely to Gloeochrysis litoralis Anand and G. maritima Anand (Anand, 1937) was observed to produce swarmers of the ochromonad type, comparable with Ochromonas oblonga Carter (Carter, 1937), in contrast to the Chromulina-likc motile cells described for the type species of Gloeochrysis, G. pyrenigera Pasch.…”
Section: Discussionmentioning
confidence: 99%
“…It may be said that microscopy led to the discovery of animicules (heterotrophic protists) and single-celled algae (microalgae or photosynthetic protists), and they joined larger animals and plants as subjects to be catalogued and classified (Patterson 1999). Electron microscopy, another technological breakthrough, revealed even greater morphological diversity among small phytoplankton and other protists (Parke and Dixon 1964). Similarly, while large bacteria associated with animals are evident using fairly standard microscopy, bacterioplankton in the ocean were thought to be limited in abundance until the widespread application of fluorescence microscopy showed that there were about one million tiny cells in every milliliter of water (Hobbie et al 1977).…”
Section: Introductionmentioning
confidence: 99%
“…A partir des dessins faits à main levée, de la description basée sur les caractères morphologiques et des mesures de dimensions, une identification des taxa a été faite en comparant nos données à certains travaux comme ceux de Naskar et al (2008), Crispino et Sant'Anna (2006), Nogueira et al (2001), Da Rodda et Parodi (2005, BerardTherriault et al (1999), Silva et al (1996), Abbott et al (1992), D'hont et Coppejan (1988) et Park et Dixon (1964). …”
Section: Identification Des Spécimensunclassified